Factores de riesgo para el desarrollo de pterigion primerio en Iquitos 2022 - Jara Souza, Salomón (2022)
Pterygium is one of the ophthalmological diseases that affects a large part of the population and the long-term repercussions can be permanent if not treated in time, even more so in an environment where ophthalmological health is underestimated. PURPOSE: This research study plans to search for the main risk factors associated with the development of primary pterygium. METHODOLOGY: It is an observational, cross-sectional and analytical study that includes 110 participants who came to the outpatient clinic of the ophthalmology service of a level III hospital in the city of Iquitos from April to July 2022. To the participants, to the leaving the outpatient clinic, they were given a questionnaire with the questions according to the study variables. RESULTS: Of the 110 study participants, 96 of them had the disease (87.3%). In addition, male sex, age over 40 years, exposed occupation, rural residence were the most frequent sociodemographic factors. The bivariate analysis shows that the factors with significant association were place of rural origin (p = 0.004), exposed occupation (p = 0.008), level of education (p = 0.014), exposure to UV rays greater than 5 hours (p = 0.005), family history (p = 0.008), dry eye (p = 0.005), astigmatism (0.005). Crossing these results in the binary logistic regression analysis shows that family history (p = 0.049; OR = 5.831), exposure time greater than 5 hours (p = 0.031; OR = 17.902), dry eye (p = 0.026; OR = 9.713) and astigmatism (p = 0.015; OR = 15.891) were significantly associated with pterygium. CONCLUSIONS: The main risk factors associated with the development of primary pterygium in this study are prolonged exposure to solar radiation for more than 5 hours in daily activities, history of pterygium in the family and the presence of dry eye. Astigmatism was not considered as a risk factor, but as one of the complications of the pterygium.